Out-of-pocket expenses and time spent on clinic visits among HIV pre-exposure prophylaxis users and other clinic attendees in Eswatini - Kohler, Stefan; Dalal, Shona; Hettema, Anita; Matse, Sindy; Bärnighausen, Till; Paul, Nicolas (Aids and behavior, 2023)
User costs constitute a barrier to the uptake of HIV pre-exposure prophylaxis (PrEP), but their magnitude appears rarely assessed. In this prospective observational study, we assessed self-reported out-of-pocket expenses (OOPE) and time spent on clinic visits during a PrEP demonstration project in Eswatini. At six public primary care clinics, 240 PrEP users and other clinic attendees were interviewed after a clinic visit. Among the 79.2% of clinic attendees reporting any medical OOPE (e.g., expenses for consultations or drugs) and/or non-medical OOPE (e.g., expenses for transport, food, or phone use), the median total OOPE was $1.36 (IQR 0.91-1.96). Non-medical OOPE occurred mostly due to transport expenses. The median travel time for a clinic visit was 1.0 h (IQR 0.67-2.0). The median time spent in the clinic was 2.0 h (IQR 1.15-3.0). The median opportunity cost of a clinic visit was $7.54 (IQR 5.42-11) when valuing time spent on a clinic visit with Eswatini’s per-capita gross domestic product. Our findings can guide measures to reduce the user costs of PrEP in Eswatini and other contexts in which oral PrEP is provided through health care facilities.